Supplementary dataset to the article "Mega environment characterization of firewood species used to generate thermal energy in arid regions in Patagonia" - Palomeque, Laura Cynthia; Carcamo, Miguel Angel; Llanos, Margarita Erica; Beider, Adriana Mariela (Estación Experimental Agropecuaria Chubut, INTA, 2024)
A characterization of the biomass utilized to generate thermal energy to heat rural homes and cook meals was carried out in the region of the Central Plateau which is a large arid area located in the province of Chubut, Argentina